Air pollution, human health and the benefits of trees: a biomolecular and physiologic perspective. Issue 1 (2nd January 2021) - Mei, Patrick; Malik, Vaishali; Harper, Richard W.; Jiménez, Juan M.
ABSTRACT: It is well accepted that particulate matter (PM) can affect human health detrimentally. Chronic and prolonged exposures to particulate matter with an aerodynamic diameter ranging between 2.5 and 10 microns (PM10 ), 0.1 and 2.5 microns (PM2.5 ) and less than 0.1 microns in size (UFPM), have been associated with cardiopulmonary diseases. PM is ubiquitously present in urban settings, while primarily absent in forest environments primarily due to the direct interception of airborne pollution particles by trees. Both short- and long-term exposure to trees in forested environments is associated with lower blood pressure and inflammation, as well as enhanced immune function. Additionally, exposure to volatile organic compounds (VOCs) actively released by trees is associated with improved health through enhanced natural killer cell activity, reduced inflammatory responses, and reduced psychological stress. This article presents the results of a literature review on the harmful health effects of air pollution in urban environments, and the potential of forested environments to promote health and disease prevention.